2015
DOI: 10.1253/circj.cj-15-0149
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adventitial Vasa Vasorum and Inflammation With Coronary Hyperconstriction After Drug-Eluting Stent Implantation in Pigs In Vivo

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jpIn order to reduce the adverse effects of the first-generation DES, many efforts have been made, including the development of a newer biocompatible DES. 9 Biolimus-A9 eluting stent (BES) is one of the new-generation DES with unique characteristics, such as biodegradable polymers that are absorbed into the arterial wall approximately 6 months after stent implantation. 9-11 Although BES has recently been shown to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
1
24
0
2
Order By: Relevance
“… 36 Abnormalities in microvasculature, vasa vasorum in adventitial or perivascular fat of relatively bigger vessels including coronary arteries may contribute to atherosclerosis and functional spastic disorder. 37 , 38 Microvascular dysfunction in cardiac tissues also critically contributes to transition from compensative cardiac hypertrophy to heart failure. 39 It is well documented that vascular immaturation in tumor is associated with pathogenesis of tumor, including their growth and metastasis, and abnormalities in pericytes and their interaction with tumor ECs contribute to tumor vascular immaturation.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Abnormalities in microvasculature, vasa vasorum in adventitial or perivascular fat of relatively bigger vessels including coronary arteries may contribute to atherosclerosis and functional spastic disorder. 37 , 38 Microvascular dysfunction in cardiac tissues also critically contributes to transition from compensative cardiac hypertrophy to heart failure. 39 It is well documented that vascular immaturation in tumor is associated with pathogenesis of tumor, including their growth and metastasis, and abnormalities in pericytes and their interaction with tumor ECs contribute to tumor vascular immaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Although these outcomes were largely satisfactory, over a prolonged period, the remaining polymer has been shown to induce inflammation associated with excessive coronary artery contractions and the development of vasa vasorum. It has been suggested that these long-term events may be preventable using a bioresorbable-polymer DES, which eventually becomes a BMS, because inflammation due to the polymer is reduced after the polymer disappears [15, 16]. Regarding outcomes for bioresorbable-polymer DESs, Wöhrle et al have reported the results of vessels ≤ 2.5 mm in diameter as a subgroup analysis of the CENTURY II trial.…”
Section: Discussionmentioning
confidence: 99%
“…2 Comparison of clinical outcomes at 9 months and 2 years with RESOLUTE φ2.25 mm Fig. 3 Comparison of clinical outcomes at 9 months and 2 years with other sizes of Ultimaster DES the polymer is reduced after the polymer disappears [15,16]. Regarding outcomes for bioresorbable-polymer DESs, Wöhrle et al have reported the results of vessels ≤ 2.5 mm in diameter as a subgroup analysis of the CENTURY II trial.…”
Section: Long-term Benefits Of Bioresorbable Polymermentioning
confidence: 99%
“…Кроме того, в КА, вовлеченных в спазм, увеличивается содержание молекул адгезии, например, P-селектина [29]. Исследования на животных продемонстрировали, что имплантация стента с лекарственным покрытием может усиливать воспаление адвентиции КА и вызывать их констрикцию посредством активации ROCK [30]. Доказано, что при ВС эпи-кардиальная и периваскулярная жировая ткань также вовлечены в патогенез неспецифического воспаления [31].…”
Section: фр и патофизиологические детерминанты всunclassified